A Pedagogical Turn in French Teacher Training The Case of the History and Geography CAPES. Issue 1 (March 2015) - Delacroix, Christian; Coward, Rodney
Abstract: The "scientific" and "educational" questions raised by the relationship between research and the teaching of history have returned to the spotlight with the current reform of teacher training in France. Undertaken as part of the "Refounding the School System" project initiated in 2012 by minister of education Vincent Peillon, this reform accords a central place to pedagogical approaches and "professionalization." This article analyzes some of the issues at stake in this "pedagogical turn" for the training of history and geography teachers, particularly with regard to renewed questions about the social function of history and the recurrent challenges and reservations on the part of academic historians about binding the notions of "scientific" and "educational" together.